Transformer Models: Key Methodologies, Next Sentence Prediction, GLUE Benchmark, and Transfer Learning - Pratap Singh Barth (International Journal of Intelligent Systems and Applications in Engineering, 2020)
This research work undertakes a comprehensive examination of the nascent yet rapidly evolving landscape of Transformer-based models in Natural Language Processing. In this research work, the architectural innovations that define this paradigm shift are delved into, particularly highlighting the efficacy of the attention mechanism as a core computational unit, which has allowed for unprecedented parallel processing and contextual understanding in sequence modeling (Vaswani et al., 2017). The central subject of this investigation is the Bidirectional Encoder Representations from Transformers (BERT), a landmark model introduced in 2018, which leverages the Transformer architecture to achieve deep bidirectional representations of language (Devlin & Chang, 2018). This study critically analyzes BERT's dual pre-training objectives: Masked Language Modeling, designed to foster a rich contextual understanding by predicting occluded tokens, and Next Sentence Prediction, a novel task aimed at equipping the model with the ability to discern relationships between sentence pairs, crucial for discourse-level comprehension. This research work further assesses the instrumental role of the General Language Understanding Evaluation benchmark, established in 2018, as a standardized and challenging suite of tasks that has significantly driven progress and enabled robust comparison across diverse language understanding systems (Wang et al., 2018a, 2018b). Through this lens, the transfer learning paradigm, exemplified by BERT's pre-train and fine-tune approach, has revolutionized NLP by enabling state-of-the-art performance across numerous downstream tasks with minimal task-specific data. This paper illuminates how these interconnected methodological pillars collectively facilitate the generation of highly versatile and robust pre-trained language representations, fundamentally reshaping the trajectory of natural language understanding research and application.